(untitled) (Práxis Educativa, 2013)
In Mexico, a reflection on the links between History as a school subject and the processes of social construction of citizenship requires conceiving the object of study as only part of a much more complex process that binds it both to civic education and ethics, and to everyday forming practices of a certain school culture. It is necessary to historically locate the sources and forms of operation of each of these facets as well as the way they reinforce their training claims.Only in this way it is possible to recognize purposes, uses and limits of teaching History as it is conceived today, as well as its inability to take as an educational goalthe building of democratic notions related to a modern conception of citizenship. Keywords: Citizenship. History and its teaching. Training for democracy.